1988
DOI: 10.1111/j.1398-9995.1988.tb01628.x
|View full text |Cite
|
Sign up to set email alerts
|

Anaphylaxis to amoxycillin but good tolerance for benzyl penicillin

Abstract: Three patients are reported on who suffered anaphylactic reactions after amoxycillin (AX) treatment and challenge but tolerated benzylpenicillin (BP) parenterally and orally. Two of the three patients had positive skin tests and RAST to AX reagents but negative responses to benzyl penicilloyl (BPO) specific skin tests and RAST and the minor determinant mixture (MDM) skin test reagent. The third case was negative to all skin tests and RAST. RAST and RAST inhibition on the two positive sera suggest that the resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
2

Year Published

1990
1990
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(45 citation statements)
references
References 7 publications
1
41
0
2
Order By: Relevance
“…Blanca et al [15,16] have described cases of hypersensitivity specifically to amoxicillin with positive skin test and radioallergosorbent test results to amoxicillin and with negative skin test results to the major and minor determinants of penicillin. These results suggest that the acyl side chain may be a significant antigenic determinant apart from the penicillin nucleus [15,16,18]. Vega et al [19] described a group of patients with suspected beta-lactam allergy who demonstrated allergic reactions only to amoxicillin (30.5%), while tolerating penicillin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blanca et al [15,16] have described cases of hypersensitivity specifically to amoxicillin with positive skin test and radioallergosorbent test results to amoxicillin and with negative skin test results to the major and minor determinants of penicillin. These results suggest that the acyl side chain may be a significant antigenic determinant apart from the penicillin nucleus [15,16,18]. Vega et al [19] described a group of patients with suspected beta-lactam allergy who demonstrated allergic reactions only to amoxicillin (30.5%), while tolerating penicillin.…”
Section: Introductionmentioning
confidence: 99%
“…Given the widespread use of semisynthetic penicillins, there may be a significant number of individuals who react only to the side-chain-related haptens [15,16,17]. A number of studies on amoxicillin allergy have been performed in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…[418][419][420][421]454 . The risk is highest with first generation cephalosporins and cephalosporins that have similar R-group side chains to specific penicillins 455,456 . The risk of penicillin cross-reactivity between most second-generation (cefoxitin) and all third generation cephalosporins (cefixime, ceftriaxone) is negligible [418][419][420][421] .…”
Section: Management Of Persons Who Have a History Of Penicillin Allergymentioning
confidence: 99%
“…In 1990, Blanca et al [27,28] described a group of patients who developed severe anaphylactic reactions to AX but had good tolerance to BP. In vitro studies confirmed that these patients had IgE antibodies that preferentially recognized the AX side chain structure [29].…”
Section: Penicillin As An Alternative Treatmentmentioning
confidence: 99%